THE INFLUENCE OF INFORMATION TECHNOLOGY ADVANCEMENT, USER TECHNIQUES, AND TRAINING ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS - I Gusti Ayu Nanda Indraswari Dewi; Gede Juliarsa (Adisam Publisher, 2025)
The rapid development of technology has significantly transformed the field of information systems, directly affecting the performance of organizations. The implementation of Accounting Information Systems (AIS) has become a crucial strategy in achieving organizational goals. This study aims to empirically examine the influence of information technology advancement, user techniques, and training on the effectiveness of AIS. The research was conducted on 20 Savings and Loan Cooperatives (SLCs) in Jembrana Regency. The sampling technique used was non-probability sampling, specifically purposive sampling, with the criteria being active cooperatives that have implemented computer-based AIS. Data were collected using a questionnaire, resulting in 60 respondent answers, and were analyzed using SPSS Statistics 26. The results indicate that information technology advancement, user techniques, and training have a positive and significant effect on the effectiveness of AIS. The implications of this research highlight the importance of enhancing information technology advancements, ongoing training, and the development of user skills to improve the effectiveness of accounting information systems, thereby supporting the performance of savings and loan cooperatives and contributing to local economic growth. This study serves as empirical evidence for the Unified Theory of Acceptance and Use of Technology (UTAUT), which explains how factors such as performance expectancy, effort expectancy, social influence, and facilitating conditions contribute to the acceptance and use of accounting information systems.